A Retrospective Cross-sectional Study of Paediatric Dermatoses during the COVID-19 Pandemic in a Tertiary Care Hospital in Bengaluru, Karnataka, India - KA Rajeswari; M Geetha (JCDR Research and Publications Pvt. Ltd., 2023)
Introduction: Dermatologic conditions constitute at least 30% of all outpatient visits to paediatricians and 30% of all visits to dermatologists involve children. Skin conditions that manifest themselves during childhood and adolescence are referred as paediatric dermatoses and make up their own unique category of skin conditions. Aim: To identify the dermatological conditions which were prevalent during the Coronavirus Disease 2019 (COVID-19) pandemic in a tertiary care hospital in Bangalore. Materials and Methods: This retrospective cross-sectional study was conducted by reviewing records of Outpatient Department (OPD) of Dermatology and Paediatrics in our tertiary care center, Bengaluru from February 2020 to February 2022. The demographic details and diagnosis are recorded. The diagnosis was made according to ICD-10 (International Classification of Diseases 10th Revision) and the prevalence of different dermatoses was calculated. Mean and standard deviation was calculated for descriptive statistics. Data were statistically evaluated with IBM Social Package for Statistical Analysis (SPSS) Statistics for Windows version 26.0., IBM Corp., Chicago, IL. Results: The total number of paediatric cases attended dermatology OPD during the two year pandemic was 558. The prevalence of paediatric dermatoses in the present study was 193 (34.58%). There were 283 girls and 275 boys with Male : Female is 1:1.02. There is a female preponderance of 50.7% against 49.28%. The majority was infectious lesions 153 (27.41%), congenital dermatoses 9 (1.61%), Papulosquamous disorders 23 (4.12%), Pilosebaceous disorders 111 (19.89%), dermatitis 193 (34.58%) followed by Miscellaneous 69 (12.36%). Conclusion: This study was conducted during COVID-19 pandemic which in comparison to the other studies shows a similar distribution of dermatoses. But there was a significant shift of age group affected which can be well explained by the lockdown and social isolation.